2024
DOI: 10.1111/dmcn.15842
|View full text |Cite|
|
Sign up to set email alerts
|

Visual, perceptual functions, and functional vision in children with unilateral cerebral palsy compared to children with neurotypical development

Monica Crotti,
Els Ortibus,
Lisa Mailleux
et al.

Abstract: AimTo investigate visual (perceptual) function and functional vision in children with unilateral cerebral palsy (CP) and children with neurotypical development (NTD).MethodFifty children with unilateral CP (mean age 11 years 11 months, SD 2 years 10 months, range 7–15 years; 27 males; 26 left‐sided unilateral CP; Manual Ability Classification System [MACS] levels: I, 27; II, 16; III, 7) and 50 age‐ and sex‐matched children with NTD participated in a cross‐sectional study. Visual acuity, stereoacuity, and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…We could hypothesize that parents of children with uCP have the tendency to underestimate the presence of VI of their children due to the diagnosis of the motor impairments which are more prominent and visible in daily life. Nevertheless, no information on the direction (worse or better visual function reported by parents) can be inferred from our analysis and further research is warranted to further understand the speci city of the FCVIQ in detecting VI in children with uCP(Crotti et al, 2024).Overall regression models did not show a strong performance of visual functions and functional vision in predicting bimanual function. The Kinarm circuit task was the only model showing a large predictive performance.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…We could hypothesize that parents of children with uCP have the tendency to underestimate the presence of VI of their children due to the diagnosis of the motor impairments which are more prominent and visible in daily life. Nevertheless, no information on the direction (worse or better visual function reported by parents) can be inferred from our analysis and further research is warranted to further understand the speci city of the FCVIQ in detecting VI in children with uCP(Crotti et al, 2024).Overall regression models did not show a strong performance of visual functions and functional vision in predicting bimanual function. The Kinarm circuit task was the only model showing a large predictive performance.…”
mentioning
confidence: 63%
“…Functional vision was assessed using the Flemish cerebral visual impairment questionnaire (FCVIQ) (Ortibus et al, 2011), a 46-item binary-response screening tool lled by the caregivers. Our previous ndings (Crotti et al, 2024) showed that children with uCP do not show large variability on the FCVIQ data when grouped into the ve factors described in the literature (Ben Itzhak et al, 2020). Furthermore, no signi cant difference was found between the ve FCVIQ factors between children with uCP with MACS-level I, II and III.…”
Section: Functional Visionmentioning
confidence: 94%
See 3 more Smart Citations